2020
DOI: 10.1371/journal.pcbi.1007803
|View full text |Cite
|
Sign up to set email alerts
|

Methodological challenges in translational drug response modeling in cancer: A systematic analysis with FORESEE

Abstract: Translational models directly relating drug response specific processes that can be observed in vitro to their in vivo role in cancer patients constitute a crucial part of the development of personalized medication. Unfortunately, current studies often focus on the optimization of isolated model characteristics instead of examining the overall modeling workflow and the interplay of the individual model components. Moreover, they are often limited to specific data sets only. Therefore, they are often confined b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…clinical in vivo responses to treatments), rather than merely drug efficacies in established cell lines (in vitro responses), as the former enables straightforward translational precision oncology applications and drug repurposing opportunities. A recent systematic analysis investigated the importance of a number of modeling components for the clinical treatment response prediction of cancer patients [115]. As expected, the sample size of the patient response data was found as an important determinant for the predictive modeling, along with experimental noise within the data that can easily deteriorate the models' robustness.…”
Section: Algorithms For Cell and Tissue-based Drug Response Predictionsmentioning
confidence: 72%
See 1 more Smart Citation
“…clinical in vivo responses to treatments), rather than merely drug efficacies in established cell lines (in vitro responses), as the former enables straightforward translational precision oncology applications and drug repurposing opportunities. A recent systematic analysis investigated the importance of a number of modeling components for the clinical treatment response prediction of cancer patients [115]. As expected, the sample size of the patient response data was found as an important determinant for the predictive modeling, along with experimental noise within the data that can easily deteriorate the models' robustness.…”
Section: Algorithms For Cell and Tissue-based Drug Response Predictionsmentioning
confidence: 72%
“…Rather surprisingly, the in vitro drug treatment profile was not among the most predictive feature when predicting the clinical response of the same drug in actual cancer patients. These results indicate that even cell line models of high accuracy do not necessarily translate to accurate predictions of drug response processes in cancer patients in vivo [115].…”
Section: Algorithms For Cell and Tissue-based Drug Response Predictionsmentioning
confidence: 96%
“…Concluding that the most important modelling factor is the choice of features and agreeing with Costello et al on the dominance of gene expression data, they rate the choice of algorithm as the third most important modelling factor. Expanding on this concept of systematically identifying optimal choices in distinct steps of the modelling pipeline and applying it to translational modelling, Turnhoff et al have published an R package that can be used to perform even more intricate analyses in the context of predicting clinical responses while training on cell line data [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are likely several contributing factors to explain this skew. First, regarding the translational models, it has been shown that well performing computational models are not necessarily specific to a drug of interest [ 38 ]. That is, general mechanisms of drug response, such as factors associated with multi-drug resistance, are likely encoded in many of the independent models and as such might skew the imputed distribution of all the drugs in a similar direction.…”
Section: Discussionmentioning
confidence: 99%